2013
DOI: 10.1530/eje-13-0037
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group protein B1: a new biomarker of metabolic syndrome in obese children

Abstract: Introduction: Obesity is associated with a chronic low-grade inflammation. High-mobility group box 1 protein (HMGB1) plays a key role in inflammation and immunostimulatory and chemotactic processes. The aim of the study was to assess the role of HMGB1 in obese children and to evaluate its diagnostic profile in identifying childhood obesity-related complications, such as the metabolic syndrome (MS). Patients and methods: Sixty obese children were enrolled and compared with 40 healthy children (control). Homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 41 publications
4
38
0
1
Order By: Relevance
“…Many studies have shown the positive correlation between circulating HMGB1 levels and BMI [8][9][10] and it has been also reported that the expression of HMGB1 in adipose tissue is altered in case of obesity. 3,8,11 This difference in HMGB1 expression has been attributed to inflammation insofar as it triggers HMGB1 secretion from cells derived from the stromal fraction of adipose tissue (ASCs), whereas mature adipocytes do not contribute to this secretion.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have shown the positive correlation between circulating HMGB1 levels and BMI [8][9][10] and it has been also reported that the expression of HMGB1 in adipose tissue is altered in case of obesity. 3,8,11 This difference in HMGB1 expression has been attributed to inflammation insofar as it triggers HMGB1 secretion from cells derived from the stromal fraction of adipose tissue (ASCs), whereas mature adipocytes do not contribute to this secretion.…”
Section: Discussionmentioning
confidence: 97%
“…25,56 In humans, several hormone molecules, including insulin and insulin-like growth factor I (IGF-I), 57 leptin, 58 adiponectin, 59 ghrelin, 60 obestatin, 61 and resistin, 62 seem to be involved in the development of obesity. Precisely, through inflammatory factors (e.g., interleukin (IL)-6 and TNF-alpha), also found in human breast-milk, 63,64 these hormonal molecules influence fat and lean body mass development in healthy term infants, 63,64 and enhance appetite signalling, 25 promoting child satiety-responsiveness and decreasing over-eating risk. 65 …”
Section: Breast-feeding and Obesity: Possible Mechanisms Involvedmentioning
confidence: 99%
“…Vitamin A has been shown to induce expression of neurosteroids in glial cell lines, which could also theoretically interact with MR(s) [99]. Additionally, human fat, an active endocrine tissue, secretes various cytokines and aldosterone-releasing factors, providing another possible link to elevated ICP in obese patients with IIH (in addition to the link of aldosterone-related predisposition to arterial hypertension, insulin resistance, and metabolic syndrome in the obese population) [50, 100, 101]. …”
Section: Hyperaldosteronism and The Paediatric Brainmentioning
confidence: 99%